2020
DOI: 10.1002/mrd.23338
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of uterine genes during the peri‐implantation period, and its relationship to the maternal brain in gestating mice

Abstract: We conducted an integrated analysis of gene expression and chromatin structure of mouse uterus to understand the regulation of uterine-expressed genes on gestation day 4 (GD4) during the peri-implantation period. The genes expressed in the uterus showed a significant association (p < .0001) with the presence of the nucleosomefree region (open chromatin) in the 5′-untranslated region of the genes. The majority of these upstream open chromatins harbored a common class of regulatory elementsknown as upstream open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…RNA-seq data analysis . The analysis of RNA-seq data was performed as described in our earlier studies [ 10 , 45 ]. Briefly, the quality of raw sequences was checked with FastQC (Version 0.11.9, Babraham Institute, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…RNA-seq data analysis . The analysis of RNA-seq data was performed as described in our earlier studies [ 10 , 45 ]. Briefly, the quality of raw sequences was checked with FastQC (Version 0.11.9, Babraham Institute, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…RNA-seq data analysis was performed as described earlier. 116 , 117 Briefly, the quality of raw sequences was checked by FastQC followed by trimming the adaptors from the sequence reads by cutadapt . The trimmomatic tool was used to perform base quality trimming (Phred score >30) by sliding window scan (4 nucleotides).…”
Section: Methodsmentioning
confidence: 99%
“…This was performed using the R package CCA . 5 The receptor and ligand genes 56 , 116 were identified from the database developed by Ramilowski et al . 55 Hierarchical cluster analysis was performed using the R package Dendextend .…”
Section: Methodsmentioning
confidence: 99%
“…This process is particularly marked in cells of the immune system (4,5). Additionally, recent work by Behura et al (6) showed that the expression of genes of the receptors and their ligands in uterine and brain tissues at the preimplantation period of pregnancy is related. The mechanism of signal transmission from the uterus to the brain remains unknown.…”
Section: Introductionmentioning
confidence: 99%